Rearrange:

Rearrange the equation by subtracting what is lớn the right of the equal sign from both sides of the equation : 3*x*(12*x-4)-9*x*(4*x-3)-(30)=0

Step by step solution :

Step 1 :

Equation at the kết thúc of step 1 :

((3x • (12x - 4)) - 9x • (4x - 3)) - 30 = 0

Step 2 :

Step 3 :

Pulling out lượt thích terms :3.1 Pull out like factors:12x - 4=4•(3x - 1)

Equation at the end of step 3 :

(12x • (3x - 1) - 9x • (4x - 3)) - 30 = 0

Step 4 :

Step 5 :

Pulling out lượt thích terms :5.1 Pull out lượt thích factors:15x - 30=15•(x - 2)

Equation at the over of step 5 :

15 • (x - 2) = 0

Step 6 :

Equations which are never true:6.1Solve:15=0This equation has no solution. A a non-zero constant never equals zero.

Solving a Single Variable Equation:6.2Solve:x-2 = 0Add 2 to lớn both sides of the equation:x = 2

One solution was found :

x = 2




Bạn đang xem: A 3x

Why learn this

*

Terms và topics

*

Related links

*

abc
a
x
y
/
|abs|
( )
7
8
9
*
4
5
6
-
%
1
2
3
+
0
,
.
=
abc
a
b
c
d
e
f
g
h
i
j
k
l
m
n
o
p
q
r
s
t
u
v
w
x
y
z

.
*



Xem thêm: Các Dạng Bài Tập Tụ Điện Có Lời Giải, Tụ Điện Phẳng Mắc Nối Tiếp Và Song Song

Back to đứng top